Soluble Ig-Like Transcript 3 Inhibits Tumor Allograft Rejection in Humanized SCID Mice and T Cell Responses in Cancer Patients - Nicole Suciu‐Foca; Nikki Feirt; Qing-Yin Zhang; George Vlad; Zhuoru Liu; Hana Lin; Chih‐Chao Chang; Eric Ho; Adriana I. Colovai; Howard L. Kaufman; Vivette D. D’Agati; Harshwardhan M. Thaker; et al. (2007)
Abstract Attempts to enhance patients’ immune responses to malignancies have been largely unsuccessful. We now describe an immune-escape mechanism mediated by the inhibitory receptor Ig-like transcript 3 (ILT3) that may be responsible for such failures. Using a humanized SCID mouse model, we demonstrate that soluble and membrane ILT3 induce CD8+ T suppressor cells and prevent rejection of allogeneic tumor transplants. Furthermore, we found that patients with melanoma, and carcinomas of the colon, rectum, and pancreas produce the soluble ILT3 protein, which induces the differentiation of CD8+ T suppressor cells and impairs T cell responses in MLC. These responses are restored by anti-ILT3 mAb or by depletion of soluble ILT3 from the serum. Immunohistochemical staining of biopsies from the tumors and metastatic lymph nodes suggests that CD68+ tumor-associated macrophages represent the major source of soluble ILT3. Alternative splicing, resulting in the loss of the ILT3 transmembrane domain, may contribute to the release of ILT3 in the circulation. These data suggest that ILT3 depletion or blockade is crucial to the success of immunotherapy in cancer. In contrast, the inhibitory activity of soluble ILT3 on T cell alloreactivity in vitro and in vivo suggests the potential usefulness of rILT3 for immunosuppressive treatment of allograft recipients or patients with autoimmune diseases.